HUBUNGAN KELENGKAPAN DAN KEJELASAN PENULISAN DIAGNOSA TINDAKAN DENGAN KETEPATAN KODE TINDAKAN MEDIS DI RUMAH SAKIT X - Maisharoh Maisharoh; Dian Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The correctness of the code is the conformity of the code of action diagnosis determined by the coding officer with the patient's medical record in accordance with ICD-9. Based on the results of observations, coders in coding still found inaccuracies in coding medical records, one of which was inaccuracy in coding medical procedures. This study aims to find out the relationship between the clarity and completeness of action writing and the accuracy of the coding of medical procedures at hospital x. The research was carried out from July to August 2022 quantitatively with a cross sectional approach. The research was conducted by observing medical records. Computerized data processing with univariate and bivariate data analysis. The results of the study found, from 86 medical records, it was clear that 82.6% of diagnoses were legible, 17.4% of diagnoses were illegible. Completeness of writing diagnostics 70.9% complete, 29.1% incomplete. Action coding accuracy 68.6% correct action coding, 31.4% incorrect. Pvalue = 0.000, which means (P ≤ 0.05). It was concluded that the clarity and completeness of writing can affect coding, where unclear writing such as using abbreviations and cursive makes it difficult for officers to read the diagnosis, so officers must first clarify to responsible party before generating the diagnostic code. In the future, it is hoped that the responsible medical staff will write down the diagnosis of the action clearly and completely, and the coder will do the coding carefully.Keywords: Clarity, Completeness, Code Accuracy, ICD-9 CM with great care.